Trito-Isaiah, penitential prayer and apocalypticism - Venter, Pieter Michiel 1947- (2012)
An analysis of the research on the compositional development of Isaiah 56-66 indicates that theredefinition of Judean identity played a major role in the formation of these chapters. Scholarsvery often refer to the penitential prayer in Isaiah 63:7-64:11 to indicate this redefinitionof identity. A study of the background of these chapters shows that Hanson’s theory of adeveloping apocalypticism is usually upheld, whilst his identification of a Zadokite oppositionis either rejected or replaced by an acknowledgement that it is not possible to identify theseopponents. The suggestion of this article is that the term ‘qualified inclusivism’ can be used asthe mark of those responsible for this section of the book of Isaiah.
Keywords: Trito-Isaiah; Apocalyptic; Apocalypticism; Prayer